GRAVEL AUGMENTATION INCREASES SPAWNING UTILIZATION BY ANADROMOUS SALMONIDS: A CASE STUDY FROM CALIFORNIA, USA. (22nd June 2013) - Zeug, S. C.; Sellheim, K.; Watry, C.; Rook, B.; Hannon, J.; Zimmerman, J.; Cox, D.; Merz, J.
ABSTRACT Anadromous salmonid diversity and abundance worldwide have been adversely impacted by anthropogenic forces, and millions of dollars are spent each year on stream habitat restoration and enhancement. However, there is a paucity of data comparing site use by salmonids before and after enhancement implementation, and few studies examine the specific environmental conditions that determine whether salmonids utilize an enhanced site. This study examines the use of gravel augmentation to improve spawning site utilization by Chinook salmon (Oncorhynchus tshawytscha) and steelhead trout (Oncorhynchus mykiss) on the Lower American River, California, USA. Spawning increased across all augmentation sites for both species, although there were species‐specific and year‐specific differences in the degree to which a site was utilized and in the spatial distribution of redds in relation to substrate size, habitat features and other redds. There were also differences in redd architecture across sites that were related to differences in gravel size. This study illustrates that gravel augmentation projects can enhance spawning habitat for salmonids where spawning beds have degraded but that species‐specific and site‐specific attributes and gravel size can influence the relative effectiveness of a project. Copyright © 2013 John Wiley & Sons, Ltd.